Perbandingan konsentrasi kadar vitamin C jeruk nipis (Citrus aurantiifolia) dan cabai rawit hijau (Capsicum frutescens L.) - Fitriyah, Izza Nailatul (Maliki Interdisciplinary Journal, 2024)
Humans need food as a source of energy to maintain their survival. Food components that must be consumed by humans to increase immunity are vitamins. Vitamins are important components needed by the body and function as a support system for the body's activities. Vitamin C is a type of vitamin that humans need to help metabolize energy in the body. This study aims to determine the comparison and difference in vitamin C levels of lime and green cayenne pepper. This study used a quantitative analysis method with the titration method. The results showed that the content of vitamin C in lime was significantly different from chili, with a value of 1.2% compared to 0.84%.